-2x-8=-13x-4

Simple and best practice solution for -2x-8=-13x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-8=-13x-4 equation:


Simplifying
-2x + -8 = -13x + -4

Reorder the terms:
-8 + -2x = -13x + -4

Reorder the terms:
-8 + -2x = -4 + -13x

Solving
-8 + -2x = -4 + -13x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '13x' to each side of the equation.
-8 + -2x + 13x = -4 + -13x + 13x

Combine like terms: -2x + 13x = 11x
-8 + 11x = -4 + -13x + 13x

Combine like terms: -13x + 13x = 0
-8 + 11x = -4 + 0
-8 + 11x = -4

Add '8' to each side of the equation.
-8 + 8 + 11x = -4 + 8

Combine like terms: -8 + 8 = 0
0 + 11x = -4 + 8
11x = -4 + 8

Combine like terms: -4 + 8 = 4
11x = 4

Divide each side by '11'.
x = 0.3636363636

Simplifying
x = 0.3636363636

See similar equations:

| -5=25x | | -16x=224 | | 111n-9=5n+27 | | 15*15x=144 | | (2x+3)x(3x-6)= | | 1.5(2a+1)=5(0.5a+0.3)+0.1 | | (0.8g+0.6-0.3)=(0.1-0.2h+0.8g) | | -x-5=3x+19 | | x^2+4*x-7=2*x-4 | | 2x-20=2x+10 | | 5x+(-2)=20 | | (5x-9)(2x+4)= | | -22=-7+3y | | -59+3x=2x+21 | | 5(0)+y=20 | | -7(-5n-2)=119 | | 42=34+q | | Log(x-6)=2 | | -1+6y=14 | | 8(4)(7)-9(3)+4(4)= | | 7x+5=5x-5 | | 10010001001002030+3-10= | | 3x+5=-8(6-5x) | | 11x-47-x=103 | | 4v=8v+32 | | 10m+12n+5m+3n+35= | | 2x-42-7x=84 | | 5x+2(1.5)=10 | | 49-9x+5x=27 | | 10000000000000000000000000000+e= | | 12-7x+4x=27 | | x+7.8=3 |

Equations solver categories